2022
DOI: 10.1021/acs.joc.2c02185
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Isotopic Atropisomers based on ortho-CH3/CD3 Discrimination and Their Structural Properties

Abstract: N–C axially chiral 3-(2-trideuteriomethyl-4,6-dimethylphenyl)-2-ethylquinazolin-4-ones and 3-(2-trideuteriomethyl-4,6-dimethylphenyl)-2-(1-phenylpropan-2-yl)­quinazolin-4-ones were prepared in high enantio- and diastereomeric purities (98% ee). These quinazolinone derivatives are isotopic atropisomers based on ortho-CH3/CD3 discrimination and were revealed to possess a slight optical rotation and high rotational stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Thus, since the verification of isotopic atropisomerism in 2 was difficult, the conversion to a diastereomeric derivative was subsequently investigated. We previously found that, in the NMR spectra of diastereomeric quinazolinone derivatives ( P,S )- VI and ( P,R )- VI possessing an asymmetric carbon atom and CH 3 /CD 3 isotopic atropisomerism, the chemical shifts of hydrogens and carbon in the ortho -methyl group clearly differ between the diastereomers due to the anisotropic effect by the benzene ring of the benzyl group on the asymmetric carbon . On the basis of this result, diastereomeric quinazolinones ( P,S )- 4 and ( P,R )- 4 were prepared (Scheme ).…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Thus, since the verification of isotopic atropisomerism in 2 was difficult, the conversion to a diastereomeric derivative was subsequently investigated. We previously found that, in the NMR spectra of diastereomeric quinazolinone derivatives ( P,S )- VI and ( P,R )- VI possessing an asymmetric carbon atom and CH 3 /CD 3 isotopic atropisomerism, the chemical shifts of hydrogens and carbon in the ortho -methyl group clearly differ between the diastereomers due to the anisotropic effect by the benzene ring of the benzyl group on the asymmetric carbon . On the basis of this result, diastereomeric quinazolinones ( P,S )- 4 and ( P,R )- 4 were prepared (Scheme ).…”
mentioning
confidence: 91%
“…Indeed, in enantioenriched compounds VII – X , their optical rotations were not detected. From the viewpoint of further development of isotopic atropisomeric chemistry based on the N–C axially chiral quinazolinone scaffold, , we were curious about 3-arylquinazolin-4-one derivatives bearing ortho - 12 CH 3 and 13 CH 3 groups. In this paper, we report on the asymmetric synthesis of atropisomeric 3-(2- 13 C-methyl-4,6-dimethylphenyl)­quinazolin-4-ones 2 and 4 , and the verification of their atropisomerism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several interesting examples have been reported in the literature (compounds A−F in Scheme 1) and different chiroptical tools have been used to characterize them. 5,6 It should be noted that the vast majority of chiral isotopologues studied concern molecules with asymmetric carbons (compounds B, C, D, and F). Conversely, chiral isotopologues with an inherent chiral structure are much less common and only a few examples have been reported so far (see for example compounds A and E).…”
mentioning
confidence: 99%